2018
DOI: 10.3390/md16090291
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of Sulfated Glucuronomannan Oligosaccharides and Their Antioxidant Activity

Abstract: Glucuronomannan oligosaccharides (Gs) were derived from fucoidan, which was extracted from the brown alga Sargassum thunbergii. Sulfated glucuronomannan oligosaccharides (SGs) were obtained by the sulfation of Gs. NMR techniques were used to reveal that the order of sulfation was Man-C6 > Man-C4 > Man-C1R > GlcA-C3 > Man-C3 > GlcA-C2. Finally, the antioxidant activities (hydroxyl radical scavenging activity, superoxide radical scavenging activity, reducing power and DPPH radical scavenging activity) of Gs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Results of HPLC analysis confirmed that GM1, GM2, GM3 and GM4 were relatively pure. Their structures were previously elucidated [ 21 , 22 ]. These glucuronomannan oligosaccharides were composed of a repeating disaccharide unit of 4-linked gluconic acid (GlcA) and 2-linked mannose (Man).…”
Section: Resultsmentioning
confidence: 99%
“…Results of HPLC analysis confirmed that GM1, GM2, GM3 and GM4 were relatively pure. Their structures were previously elucidated [ 21 , 22 ]. These glucuronomannan oligosaccharides were composed of a repeating disaccharide unit of 4-linked gluconic acid (GlcA) and 2-linked mannose (Man).…”
Section: Resultsmentioning
confidence: 99%
“…Several factors determine the antioxidant activity of fucoidan, including concentration, Mw, the degree of sulphation, substitution groups and their positions, type of sugar, and glycosidation branching [59,60,61]. It has been shown that components isolated from brown algae exhibit ROS scavenging activity in a concentration-dependent manner [62].…”
Section: Classical Activities Of Fucoidanmentioning
confidence: 99%
“…SPSJ is a highly branched, partially acetylated, sulfated galactofucan, built up of (1→3)-α-L-fucose residues, while SPUP is a partially acetylated, highly sulfated galactofucan consisting of (1→3)- or (1→3); (1→4)-α- l -fucose residues [ 30 ]. Meanwhile, SPSH is established to consist mostly of the repeating → 3-α- l -Fuc p (2SO 3 − )-1 → 4-α- l -Fuc p (2,3SO 3 − )-1 → fragment with insertions of the →3-α- l -Fuc p (2,4SO 3 − )-1 → fragment and unsulfated side chains with the α-L-Fuc p -1 → 2-α- l -Fuc p -1 → structure connected to the main one at C4 of the monosaccharide residue [ 31 ]. SPCF is composed of highly sulfated 3-linked β- d -galactopyranose and β- l -arabinopyranose residues [ 32 ].…”
Section: Discussionmentioning
confidence: 99%